Automated quantification of EEG spikes and spike clusters as a new read out in Theiler's virus mouse model of encephalitis-induced epilepsy - Anjum, Syed Muhammad Muneeb; Kaeufer, Christopher; Hopfengärtner, Rüdiger; Waltl, Inken; Broeer, Sonja; Loescher, Wolfgang (Epilepsy and Behavior, 2018)
Intracerebral infection of C57BL/6 mice with Theiler's murine encephalomyelitis virus (TMEV) replicates many features of viral encephalitis-induced epilepsy in humans, including neuroinflammation, early (insult-associated) and late (spontaneous) seizures, neurodegeneration in the hippocampus, and cognitive and behavioral alterations. Thus, this model may be ideally suited to study mechanisms involved in encephalitis-induced epilepsy as potential targets for epilepsy prevention. However, spontaneous recurrent seizures (SRS) occur too infrequently to be useful as a biomarker of epilepsy, e.g., for drug studies. This prompted us to evaluate whether epileptiform spikes or spike clusters in the cortical electroencephalogram (EEG) may be a useful surrogate of epilepsy in this model. For this purpose, we developed an algorithm that allows efficient and large-scale EEG analysis of early and late seizures, spikes, and spike clusters in the EEG. While 77% of the infected mice exhibited early seizures, late seizures were only observed in 33% of the animals. The clinical characteristics of early and late seizures did not differ except that late generalized convulsive (stage 5) seizures were significantly longer than early stage 5 seizures. Furthermore, the frequency of SRS was much lower than the frequency of early seizures. Continuous (24/7) video-EEG monitoring over several months following infection indicated that the latent period to onset of SRS was 61 (range 16-91) days. Spike and spike clusters were significantly more frequent in infected mice with late seizures than in infected mice without seizures or in mock-infected sham controls. Based on the results of this study, increases in EEG spikes and spike clusters in groups of infected mice may be used as a new readout for studies on antiepileptogenic or disease-modifying drug effects in this model, because the significant increase in average spike counts in mice with late seizures obviously indicates a proepileptogenic alteration.
EVALuna2:204313